Doenças hepáticas: aprendizado baseado em 2000 transplantes de fígado - Garcia, Huygens (2022)
A practical book, pleasant reading, useful for students, residents, doctors and other health professionals. Based on real clinical cases, composed of 57 chapters, where the main liver diseases that can evolve with the need for transplantation are addressed.